The impact of leadership competency among Malaysian academician during industrial attachment: Malaysian case study - S., Ahmad Sabri; A., Mohd Yusof; S., Ya'acob; N., Mohd Abbas; Z., Abal Abas; R., Azmi; W.O.A.S., Wan Ismail (2021)
Leadership skills are essential in ensuring effective management in a team of an organisation. Lack of skills could cause communication issues. conflicts. low motivation, low morale of employees and many other damaging factors towards an organization. The impact of effective or powerful leadership has proven towards a positive gain or feedback in return including profit a reputation perspectives. In certain circumstances. effective leadership is important to manage changes when change is the only method in sustaining an organisation in the current business environment. In managing crisis. good leadership could prevent or reduce the damage that occurred from various aspects. Such skills are significant for any types of the organization including the academia and the industry as well. Due to that. there is a need in collaborating both fields in order to exchange the expertise they have in hand to be shared to the students in the education field and with the employees in an organisation. The collaboration is hoped to exchange the knowledge the academicians have and the experience from the real industry particularly in the perspective of leadership. This paper focuses on the Leadership Competency model that has been developed by the Higher Education Leadership Academy(AKEPT) which listed five clusters of leadership skills namely; personal effectiveness, cognition. leading others. impact & influence and achievement action which comprise another 15 smaller leadership elements under the competencies' Model. Therefore, this paper aims to answer one main question: How much leadership competencies elements have been learned during this programme? To achieve the aim, this paper is broken down into three research objectives: (i) to identify the leadership competencies elements have been learned during this programme, (ii) to rank the leadership competency elements based on output (i), and (iii) to benchmark the output from (ii) to the Leadership Competency Model. Based on the case study of Industry-Academia Collaboration Program by Ministry of Higher Education Malaysia, the data of this study were collected from 52 selected academicians that attached to the respective leader in the industries related to their professional expertise As the result, this paper highlights the leadership perspective gained from the six-month-attachment observation and life experience with the leaders in the organisations. Then, the rank shows the most applied leadership skills according to the Leadership Competency model used in this study. Finally, the benchmarking identifies the gap and help to upskill or improve the leadership skills in both the academic world and the Industry. Moreover. the findings could contribute to the values of attachment between both fields that complement one another in a win-win situation. The benefits of effective leadership will help to generate Influential leaders who will result In a better future of an organization.